Diamond Fraud Analysis In Detecting Fraud In Financial Reports Using The Beneish M-Score Model (Empirical Study of LQ-45 Companies Listed on the Indonesia Stock Exchange 2018-2022) - Mairahni Dewi; Sri Wineh; Gita Suliska (PT. Anagata Sembagi Education, 2025)
This study aims to determine the effect of diamond Fraud on the occurrence of financial statement fraud in the company. Independent variables used in this study are Financial targets, Financial Stability, External Pressure, Opportunity, Rationalization, and Capability. In this study, Financial Statement fraud was measured using Beneish M-Score Model. The population used in this study is companies classified in LQ-45 listed on the Indonesia Stock Exchange (IDX) during the period 2018-2022. The method of determining the sample used in this study is to use purposive sampling method, samples obtained by 20 companies. The Data used is secondary data in the form of financial statements. Data analysis using logistic regression analysis with the help of SPSS software 29. The results of this study showed that the financial Target, Financial Stability, Opportunity, and Rationalization variables had no effect on the potential for financial statement fraud. while external Pressure and Capability variables affect the potential for financial statement fraud.